Performance of ferrierite promoted with tungsten or boron species during the linear butene skeletal isomerization - Astudillo, Alejandro (2006)
Ammonium and potassium ferrierites were modified with tungsten or boron species using incipient wetness and wet impregnation or ion exchange. Catalytic behavior during the linear butene skeletal isomerization was measured at 300 and 450ºC, at atmospheric pressure and 0.15 atm 1-butene partial pressure. At 3000C and a short time, catalysts having strong acid sites practically reach the same high butene conversion with a low isobutene selectivity. Those acid sites favor undesirable side reactions. At a long time, conversion decreases. At a short time, tungsten exchanged on potassium-ferrierite produces two times the ferrierite’s isobutene yield. At a long time, boron impregnated on ferrierite reaches the largest isobutene production. At 450ºC, the high conversion is maintained even at a long time. At this temperature, tungsten impregnated on potassium-ferrierite, sample without strong acid sites, practically produces the same isobutene yield of ferrierite, even though its conversion is only a half of the ferrierite one. By considering by-product distributions, it can be inferred that dimerization and oligomerization reactions take place. Carbonaceous deposits were characterized by temperature-programmed oxidation and FTIR. The acid strength of active sites influences the coke amount. Independent of temperature, carbonaceous deposit formed on samples with strong acid sites is between 6.0 and 7.4%. The smallest amount (1.0%) is formed on tungsten impregnated potassium-ferrierite, which only displays the low-temperature combustion peak after reaction at 300ºC. Reaction temperature and type of acid sites affect the nature of carbonaceous deposit. Both olefinic species and aromatic rings appear in the deposit formed at 300ºC; aromatic coke increases when reaction takes place at 450ºC. Isobutene dimeric species play a role in coke formation.